Hybrid fuel cell-battery-supercapacitor energy management system controlled by sliding modes - Chiacchiarini, Hector Gerardo (2022)
Hybrid Energy Storage Systems composed by more than a single energy source and/or energy storage devices can show better performance than single devices when an adequate Energy Manager System is designed. A sliding mode control is used in this paper for an energy management system of a hybrid energy source and storage system composed by a hydrogen fuel cell, a battery and a supercapacitor. The manager splits the power demand of an electric traction system over the energy source and the two storage devices, preventing the battery and the fuel cell to be stressed by fast changing current demands, thus preserving their lifespan, while responding adequately to the traction system current demand. Simulation results show adequate performance.